Kajian Tingkat Kesejahteraan Penambang Intan, Dan Alternatif Pilihan Pekerjaan Baru Apabila Area Penambangan Di Kecamatan Cempaka, Kota Banjarbaru Ditutup Pemerintah - Bayu Wijokongko; A. Rahmansyah; Soemarno Soemarno; Bambang Joko Priatmadi (Universitas Lambung Mangkurat, 2020)
Diamond miners in kec. Cempaka Banjarbaru city has long been a mainstay and provides livelihood for traditional diamond miners. However, the income and life of traditional diamond mining communities is still economically low, compared to the profits of capital owners and borrowing mining equipment. On the other hand diamond mining that ignores environmental sustainability has damaged the environment both flora and fauna, the formation of holes and ponds former mine, muddy and polluted ground water, and moderate damaged plant land so that the cause of diamond mining in Cempaka was immediately closed by the Banjarbaru municipal government. The purpose of this study is to examine: 1) analyzing the effect of activities as diamond miners on the level of welfare of the miner's family, 2) the type of new work the miner wants, and 2) the reason for the miner to move to a new job. This research was carried out for six months, located in three diamond mining areas including Ujung Murung, Lokaas and Plumpung villages in kec. Cempaka. This location was chosen because it is a community diamond mining area that represents the profile of community diamond miners in the suburbs of Banjarbaru. The research method uses a combination of survey and quantitative methods. The selection of diamond mining villages was carried out in three selected villages including Ujung Murung, Lokaas and Plumpung villages, while respondents were selected by purposive sampling 30% of the population of the village community with a total of 90 respondents consisting of 45 miners and 45 non-miners. The parameters observed were: a)) The type of new work chosen by the miners when the mining of people's diamonds was closed by the Banjarbaru local government, and b) The reason for moving to a new type of work. The results showed that the activities as diamond miners did not significantly affect the welfare of miners' families, and did not provide decent results in increasing and increasing the welfare of diamond miners. The most desirable alternative work alternatives and selected respondents respectively were chicken farming by 37.78%, followed by duck farming, rice / crops and tilapia businesses respectively by 15.56%, and the lowest was the goat raising business and fruit cultivation by 2.23%. Meanwhile the reasons respondents chose chicken raising business as the type of business most in demand or were chosen with the reasons that are: a) easy to get seeds, b) not big capital, c) easy maintenance, and d) easy and fast marketing results.